IBN SINONING LOTIN TILIGA TARJIMA QILINGAN ASARLARI VA ULARNING FAN TARIXIDAGI AHAMIYATI - Norxujayev Shaxboz Xusanjon o`g`li, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article contains brief information about the life style, scientific heritage of the great scholar and encyclopedist Abu Ali Ibn Sina, who grew up in the Middle Ages in the Middle Eastern Muslim world, in the territory of Central Asia. Also, among the scientist's works, there are opinions about the translations into Latin and how important they were for the development of science.